2014
DOI: 10.4236/ijg.2014.51011
|View full text |Cite
|
Sign up to set email alerts
|

Static Reservoir Modeling Using Well Log and 3-D Seismic Data in a KN Field, Offshore Niger Delta, Nigeria

Abstract: This study focuses on the application of 3D static model using 3-D seismic and well log data for proper optimization and development of hydrocarbon potential in KN field of Niger Delta Province. 3D Seismic data were used to generate the input interpreted horizon grids and fault polygons. The horizon which cut across the six wells was used for the analysis and detailed petrophysical analysis was carried out. Structural and property modeling (net to gross, porosity, permeability, water saturation and facies) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…According to porosity calculation, zone-4 is the most prospective gas-bearing zone with respect to zone1, 2, 3, and 5 in the study well. Some recent studies were found also similar average porosity ranged in the Laja Oil Field, Rickie Field, KN Field and Y Field, Niger delta [27][28][29][30]. For assessing Narsingdi gas productivity, the calculated average permeability values of these zones were ranged from 28 mD to 90 mD by Coates and Domanior [19] equation while average permeability values ranged From 28 mD to 40 mD was followed by Wyllie and Rose [20] equation.…”
Section: Discussionmentioning
confidence: 99%
“…According to porosity calculation, zone-4 is the most prospective gas-bearing zone with respect to zone1, 2, 3, and 5 in the study well. Some recent studies were found also similar average porosity ranged in the Laja Oil Field, Rickie Field, KN Field and Y Field, Niger delta [27][28][29][30]. For assessing Narsingdi gas productivity, the calculated average permeability values of these zones were ranged from 28 mD to 90 mD by Coates and Domanior [19] equation while average permeability values ranged From 28 mD to 40 mD was followed by Wyllie and Rose [20] equation.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating geologic, geophysical, and petrophysical data into one complete model of the whole field is an important process to help better understand the complexity of reservoir formations, thereby facilitating significant gains in productivity in terms of identifying and managing reservoirs (Zou et al, 2006;Denney, 2013;Adeoti et al, 2014). It provides reservoir engineers with a reliable and comprehensive basis upon which they can simulate and manage reservoirs (Al-Harbi et al, 2013;Karamitopoulos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The study has also created a geological model for KN field that can be updated as new data are acquired for field development. The model could be transferred to the reservoir engineer for proper characterization during simulation [2]. The quality of petrophysical analysis leads to a better reserve calculation [3][4][5].…”
Section: Introductionmentioning
confidence: 99%